Harmony in Diversity: Exploring the Positive Impacts of Ethnic Diversity on Social Integration in Islamabad, Pakistan (Journal of Asian Development Studies, 2025)
This research explores the role that ethnic diversity can play in fostering social cohesion in Islamabad, Pakistan, one of the most united cities in the world, coming from a very diverse root of cultures and traditions. The cross-sectional exploratory study explores diverse subjects concerning cultural enrichment, economic benefits, political representation, social learning, democratic values, civic participation, and community resilience. The research measures the nuanced views of dominant and minority ethnic groups through purposive sampling and qualitative methods such as in-depth interviews and focus group discussions. Resultingly, cultural infusion is identified as a key outcome using thematic analysis that enhances the city's collective identity. Ethnic diversity then catalyzes innovation, economic growth and inclusive leadership. The output also highlights the positive effect on social learning, trust building, democratic values, civic engagement, and community resilience. The implications of the findings for policymakers include supporting policies that protect cultural diversity, encourage inclusive practice, and invest in educational programs that facilitate cross-cultural understanding. It is recommended that its cultural diversity be celebrated and the economic advantages of diversity of skills be recognized.